Enhancing Blockchain Utilization Capability in Blockchain Platform: Indonesia’s Dynamic Infrastructure and Organizational Factors - Mu’min, Halek; Wahyudono, Denny Bernardus Kurnia; Kaihatu, Thomas Stefanus (Journal of Cultural Analysis and Social Change, 2025)
This study develops and validates Blockchain Utilization Capability as a novel construct that fundamentally reconceptualizes complex enterprise technology adoption by addressing critical gaps in conventional models that assume direct relationships between antecedents and behavioral intentions. Through cross-sectional survey methodology involving 300 Indonesian SMEs actively engaged with blockchain platforms, we integrate the Technology-Organization-Environment framework with the Technology Acceptance Model, positioning capability as a central mediating mechanism analyzed using PLS-SEM with bootstrapping procedures. Results reveal complete mediation patterns where organizational infrastructure, environmental pressures, technological features, perceived usefulness, and perceived ease of use operate exclusively through capability development rather than directly influencing adoption intentions. Organizational factors demonstrate large effects on capability development, while perceived ease of use exhibits paradoxical negative relationships through suppression mechanisms, with the construct achieving superior predictive performance and explaining substantial variance in adoption intentions. We introduce Capability-Mediated TAM, demonstrating that perceptual beliefs require translation into organizational capabilities before influencing complex technology adoption, bridging previously disconnected frameworks by revealing common capability-building pathways through which diverse antecedents operate, and transforming TOE from a descriptive taxonomy into a dynamic process model. Findings establish that organizations should prioritize systematic capability development through phased approaches emphasizing organizational readiness, formal governance, and cross-functional integration before pursuing production implementations, recognizing capability building as an essential rather than optional pathway to blockchain adoption.